ASSESSMENT OF PREVALENCE AND GENDER BASED DISTRIBUTION OF VARIOUS DENTAL MALOCCLUSION - A RETROSPECTIVE STUDY - Jain, Prerna; B, Nivethigaa; Ranjan, Manish (International Journal of Psychosocial Rehabilitation, 2020)
INTRODUCTION: At all social levels, well-aligned teeth and a pleasing smile reflects positive status, and irregular or protruding teeth reflect negative status. In majority, balanced facial feature is considered to be pleasing for each race and sex. Malocclusion can be defined as an occlusion in which there is mal relationship between the arches in any of the three planes or anomalies in tooth position beyond normal limits AIM: The aim of the study was to assess the prevalence and gender-based distribution of different dental malocclusion. MATERIALS AND METHODOLOGY: This was a retrospective cross-sectional study. Samples were collected from patient records from Saveetha dental college between June 2019- March 2020. Of the total case records of 41,000 patients, age sorting was done and the final 17150 patient data between the age group 18-35 years were collected. The data was collected only for patients who had all teeth present for diagnosis of molar relation. Tabulated with parameters of age, gender and dental malocclusion. It was imported to SPSS for statistical analysis. Descriptive statistics and chi square test were done. RESULTS: Out of a total of 41,000 patients, analysis showed that there were 17150 patients in the required age group of which 60.4% were males and 39.6% were females. The prevalence of male patients was more when compared to female patients and the common age group in the study analysis is 26-30 years. Class I malocclusion was found to be the most predominant dental malocclusion (94.3%) and Class II Division 2 subdivision was the least prevalent. There was a statistically significant difference in the prevalence of various dental malocclusion in male and female population with a p value of 0.000. CONCLUSION: Within the limits of the study, in both the gender, class I malocclusion was more prevalent and class II Division 2 subdivision was least prevalent.